2011
DOI: 10.1007/s00382-011-1133-y
|View full text |Cite
|
Sign up to set email alerts
|

A new method for extracting the ENSO-independent Indian Ocean Dipole: application to Australian region tropical cyclone counts

Abstract: We introduce a simple but effective means of removing ENSO-related variations from the Indian Ocean Dipole (IOD) in order to better evaluate the ENSO-independent IOD contribution to Australian climate-specifically here interannual variations in Australian region tropical cyclogensis (TCG) counts. The ENSO time contribution is removed from the Indian Ocean Dipole Mode index (DMI) by first calculating the lagged regression of the DMI on the sea surface temperature anomaly (SSTA) index NINO3.4 to maximum lags of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Similarly, Wijnands et al () showed that the IOD Mode Index (DMI) was the most commonly occurring predictor of the best‐performing models in the region. In contrast, Werner, Maharaj, and Holbrook () found that the IOD added no additional predictive value over using traditional ENSO indices (i.e., Niño 4 SST). Finally, Ramsay, Richman, and Leslie () identified a southwest‐to‐northeast dipole pattern of SST anomalies in the Indian Ocean and showed that a simple index based on this dipole resulted in improved prediction of seasonal TC counts for the region compared with models that incorporated only ENSO‐based predictors.…”
Section: Interannual Variability and Seasonal Predictabilitymentioning
confidence: 94%
“…Similarly, Wijnands et al () showed that the IOD Mode Index (DMI) was the most commonly occurring predictor of the best‐performing models in the region. In contrast, Werner, Maharaj, and Holbrook () found that the IOD added no additional predictive value over using traditional ENSO indices (i.e., Niño 4 SST). Finally, Ramsay, Richman, and Leslie () identified a southwest‐to‐northeast dipole pattern of SST anomalies in the Indian Ocean and showed that a simple index based on this dipole resulted in improved prediction of seasonal TC counts for the region compared with models that incorporated only ENSO‐based predictors.…”
Section: Interannual Variability and Seasonal Predictabilitymentioning
confidence: 94%
“…The October 2006 global SST anomaly pattern (Figure c) indicates the expected negative SST gradient from west to east across the Indian Ocean associated with a +IOD event. By several metrics, the 2006 +IOD event was one of the strongest in the 1965–2012 period [ Werner et al ., ; Wilson et al ., ]. Coexisting SST anomalies resembling El Niño occur in the equatorial Pacific Ocean [ Harrison and Larkin , ; Okumura and Deser , ].…”
Section: Resultsmentioning
confidence: 99%
“…Of a range of factors, the role of regional and remote sea surface temperatures (Dailey et al, 2009;Jin et al, 2013;Rumpf et al, 2010;Wang et al, 2011) and large-scale modes of atmospheric or oceanic variability such as El Niño-Southern Oscillation, the Madden-Julian Oscillation and the Indian Ocean Dipole (Klotzbach, 2011b(Klotzbach, , 2012Larson et al 2012;Lin et al, 2012;Werner et al, 2012) have received attention. Of course, a fundamental requirement for robust hurricane risk assessment is the availability of quality assured homogenous tropical cyclone frequency, intensity and track data.…”
Section: Extreme Climate Eventsmentioning
confidence: 99%